(untitled) (Al-Qamar, 2021)
The ancient poetic scenarios of Urdu are characterized by feminine language styles. The Sufis sought the ascension of love by using the words ‘Pitam’, ‘Pi’, ‘Piu’, ‘Sajan’, ‘Sajnan’, ‘Sanwaria’, ‘Pia’ and other similar words to recognize the real beloved. So, they expressed their views by using various poetry genres such as ‘Duhey’, ‘Jakri’, ‘Zaari’, ‘Kabit’, ‘Siviyyaa’, ‘Chhand’, ‘Ashlok’, ‘Khayal’, ‘Haqiqat’, ‘Qawwali’, ‘Makashifa’, ‘Nukta’, ‘Sahelaa’, ‘Seh Harfi’ and ‘Nazam Namey’ etc. Amir Khusrau, Sheikh Bajan, Sheikh Abdul Qudus Gangohi, Burhanuddin Janam, Khawaja Banda Nawaz, Bullhey Shah and other Sufis used the feminine language to express their feelings and demonstrated their exemplary dedication and loyalty. This effort of theirs led to the consolidation of the tradition of the feminine language. In this article, the same aspects have been researched and validated.